Membangun Umat dengan Pemahaman Al-Qur'an yang Toleran dan Moderat Strategi Melalui Pendekatan Pendidikan dalam Keluarga - Muhammad Darwis Hude (Lajnah Pentashihan Mushaf Al-Qur'an, 2008)
This writing puts its emphasis on the importance of education in the family since the family is the smallest unit in society. In addition to that; in the formal educations, the children get from the school only give standard service, whereas each child has a very special and unique character and different level of intelligence. There are three models of upbringing education, they are: authoritarian model, democratic model, and permissive model. Shifting paradigm in the family is needed to be done, that is from